SEBARAN TUMBUHAN BAWAH PADA TUMBUHAN Acacia nilotica (L) Willd. ex Del. DI SAVANA BEKOL TAMAN NASIONAL BALURAN - Suhadi Suhadi (The East Java Biological Society, 2009)
Bekol savannah is places of reproduction for banteng (Bos javanicus d` Alton), water buffalo (Bubalus bubalis L), large deer (Cervus timorensis) and green peafowl (Pavo mutiacus) and for conservation of species, habitat and genetic. In sector recreation and tourism, Bekol Savannah is object for eco-tourism, that is very attractive for local tourist or foreign and to see biodiversity of flora and fauna. Set of problems are wildlife population very low result presence Acacia nilotica (L) Willd. ex Del in savannah. This plant competitive with wildlife feeding grasslands result to descent plant diversity and biomass. The conclusion of the grassland dispersal at plant of A. nilotica (L) Willd. ex Del. in Bekol savannah Baluran National Park are: (1) The grassland dispersal at plant of A. nilotica (L) Willd. ex. Del.plot 1×1 m2 have 24 species`s with importance value of wildlife feeding grasslands = 40.49%, (2). The grassland dispersal at plant of A. nilotica (L) Willd. ex Del.plot 1x1 m2 (distance of plots 1 m from center point of stem) have 27 species`s with importance value of wildlife feeding = 29.30% and (3). Productivity wildlife feeding grasslands only of to fill 8.93% from wildlife in savannah if be found plant of A. nilotica (L) Willd. ex Del.